A fiber-array probe technique for measuring the viscosity of a substance under shock compression - 冯立鹏 刘福生 马小娟 赵北京 张宁超 王文鹏 郝斌斌 (Chinese physics B, 2013)
A fiber-array probe is designed to measure the damping behavior of a small perturbed shock wave in an opaque substance, by which the effective viscosity of substance under the condition of high temperature and high pressure can be constrained according to the flyer-impact technique. It shows that the measurement precision of the shock arrival time by using this technique is within 2 ns. To easily compare with the results given by electrical pin technique, the newly developed method is used to investigate the effective viscosity of aluminum （Al）. The shear viscosity coefficient of A1 is determined to be 1700 Pa.s at 71 GPa with a strain rate of 3.6× 10^6 s-1, which is in good agreement with the results of other methods. The advantage of the new technique over the electrical pin one is that it is applicable for studying the non-conductive substances.